ANALISA PERKEMBANGAN FASILITAS KAWASAN SAINS TEKNOLOGI BATAM (BATAM TECHNOPARK) - Dian Hari Susanto; Yuanita FD Sidabutar (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Initiative to foster innovation-driven economic growth in the Riau Islands region. This study aims to analyze the development of facilities that support the function of the park as a dynamic innovation ecosystem, focusing on infrastructure, institutional support, and the involvement of key stakeholders such as government, academia, and industry. The methodology includes literature review, field observation, and semi-structured interviews with relevant parties. The analysis reveals progress in several areas, including business incubation units, research laboratories, and collaborative spaces. However, challenges remain regarding triple helix integration and sustainable funding mechanisms. The study recommends a systemic approach to the development of science and technology park facilities, emphasizing policies that encourage synergy among stakeholders. This research is expected to contribute to the advancement of more effective and competitive science and technology zones, both regionally and nationally.